Men and women in interaction - Aries, Elizabeth (Oxford University Press, 1996)
Elizabeth Aries sees the issue as more complex and dependent on several variables, among them the person's status, role, goals, conversational partners, and the characteristics of the situational context. Aries discusses why we emphasize the differences between the sexes, the ways in which these are exaggerated, and how we may be perpetuating the very stereotypes we wish to abandon. For psychologists and researchers of gender and communication, this book will illuminate recent studies in gender relations. For general readers it will offer a stimulating counterpoint to prevailing views